Energy Transfer Under Electrical Excitation and Enhanced Electroluminescence in the Nanolaminate Yb, Er Co‐Doped Al2O3 Films. Issue 8 (7th May 2019) - Yang, Yang; Ouyang, Zhongtao; Liu, Jianzhao; Sun, Jiaming
Abstract : The energy transfer from Yb 3+ to Er 3+ ions under electrical excitation which enhances the Er‐related 1531 nm electroluminescence is evidenced, within the nanolaminate Yb, Er co‐doped Al2 O3 films fabricated by atomic layer deposition. The light‐emitting devices based on these nanolaminates present an external quantum efficiency up to 24% and the power efficiency of 2.8×10 −3, ≈60% higher than the solely Er‐doped Al2 O3 device. The decay dynamics also support, with the radiative lifetime of the Yb 3+ emission reduced while that of Er 3+ emission rises. The Er 3+ and Yb 3+ ions are impact‐excited by hot electrons, which stem from Poole–Frenkel conduction mechanism in Al2 O3 matrix. This work certifies the potential of sensitizing Er 3+ ions by the adjacent Yb 3+ ions under electrical excitation, and applications of the rare earth‐doped nanolaminates in silicon‐based optoelectronics. Abstract : The energy transfer from Yb 3+ to Er 3+ ions under electrical excitation, which effectively enhances the Er‐related 1.53 µm electroluminescence, is evidenced by the emission intensities and decay dynamics, within the nanolaminate Al2 O3 :Yb, Er films fabricated by atomic layer deposition. This co‐doped device outperforms with an external quantum efficiency up to 24% and a power efficiency of 2.8×10 −3 .